A review on synergy of cavitation and sediment erosion in hydraulic machinery - Wang, Changchang; Tan, Lei; Chen, Mendi; Fan, Honggang; Liu, Demin (Frontiers in Energy Research, 2022)
Synergy of cavitation and sediment erosion is the most severe destruction in hydraulic machinery in sediment-laden rivers, and currently the physics and mechanism are still lack of understanding. The synergy effects of cavitation and sediment erosion not only reduce the efficiency and the life of the hydraulic machinery but also cause costs in operation and maintenance. With the rapid development of renewable clean energy and the transformation of water resources, an increasing number of new hydropower stations and water diversion projects are currently planned or under construction, where most of them are in sediment-laden rivers. In the present paper, the research work including theory, experiment, and simulation, in this field carried out by various investigators are presented and discussed. Physical mechanisms involved in the synergy of cavitation and sediment erosion which is responsible for the material damage as investigated by researchers have also been discussed, and would help to identify gaps for future studies.